Apartheid digital de estudantes do Ensino Médio na educação básica pública de São Paulo - Silva, Alexandro Bento Piza da (2022)
This research aims to reflect on the structures of digital inclusion and exclusion which affects high school students in state schools in São Paulo. The study covers a period between the pre-pandemic from Covid-19, the pandemic itself and the return to faceto-face classes. What justifies this study is the fact that technology, the digital resources that were adopted or that were tried to be adopted, interfere directly in the teaching-learning process, however, their reach did not include most of the students from the outskirts. In this dissertation, the following problematizing question is sought: how can access to digital resources help in the cognitive development of students? The study was carried out using the methodology of qualitative research, of the experimental type, based on data collected in the field. For the review of previous studies, three periods were considered for each phase of the study. The pre-pandemic phase includes the period from 2019 to 2020, the pandemic phase includes the years 2020 and 2021 and the developments in early 2022, both composed of articles, thesis and dissertations from the institutions PUC’s Thesis Bank, Capes, Scielo and Google Scholar. The data collection instruments are questionnaires, observation of the socioeconomic profile of the region where the investigation took place. The theoretical framework that supports this work are the concepts of digital inclusion and exclusion and education. Digital inclusion and exclusion is based on Silveira (2005). In the field of education, we focus on the scope of active methodologies as mechanisms for transforming the educational structure based on the concepts of Moran and Bachi (2018) and on the discussion about hybrid learning. The research context involves, in different phases, 205 students from a State School located on the outskirts of the city of São Paulo, enrolled in high school. As a result, the elements acquired in the field research and in the theoretical foundation are considered to affirm the existence of a process of digital apartheid generated by the form of social organization and economic condition to which the students are subjected, also due to programs of digital inclusion that are not effective in their application and due to the lack of a formative pedagogical structure for teachers and students to take advantage of the positive effects that can come from digital tools